2018
DOI: 10.1371/journal.pbio.2003703
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of Mesolithic Scandinavia: Investigating early postglacial migration routes and high-latitude adaptation

Abstract: Scandinavia was one of the last geographic areas in Europe to become habitable for humans after the Last Glacial Maximum (LGM). However, the routes and genetic composition of these postglacial migrants remain unclear. We sequenced the genomes, up to 57× coverage, of seven hunter-gatherers excavated across Scandinavia and dated from 9,500–6,000 years before present (BP). Surprisingly, among the Scandinavian Mesolithic individuals, the genetic data display an east–west genetic gradient that opposes the pattern s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
212
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(233 citation statements)
references
References 78 publications
17
212
2
2
Order By: Relevance
“…Motivated by our observations that allele frequencies show a temporal variability over time we introduced the concept of Time 15 Informative Markers (TIMs). We showed that TIMs, like rs1393350 associated with pigmentation, have increased or decreased their frequency over time as reported elsewhere (30,37,38,40) and can be used as biomarkers for specific time periods. Based on this concept, we developed the Temporal Population Structure (TPS) tool, which utilises TIMs to date ancient skeletons as far back as the Late Upper Palaeolithic using their genomic data without prior assumptions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Motivated by our observations that allele frequencies show a temporal variability over time we introduced the concept of Time 15 Informative Markers (TIMs). We showed that TIMs, like rs1393350 associated with pigmentation, have increased or decreased their frequency over time as reported elsewhere (30,37,38,40) and can be used as biomarkers for specific time periods. Based on this concept, we developed the Temporal Population Structure (TPS) tool, which utilises TIMs to date ancient skeletons as far back as the Late Upper Palaeolithic using their genomic data without prior assumptions.…”
Section: Discussionsupporting
confidence: 84%
“…TPS date for RISE174 is 4,347-3,533 BP, consistent with the Neolithic attribution of the site. 40 Correcting the radiocarbon date at Kyndeløse, Denmark. RISE61 was radiocarbon-dated to 4,801-4,442 BP (17), which is suggestive of a Middle Neolithic origin ascribed to 5,400-4,700 BP in Scandinavia.…”
Section: Tps Application To Five Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Damlien ; Günther et al . ). From the following centuries, a number of sites from the inland in both northern Finland and Norway give evidence for a more extensive use of terrestrial resources in the birch woodlands and forests (Halinen ; Hood ).…”
Section: Results and Interpretationmentioning
confidence: 97%
“…As in recent history, plants were probably of secondary importance as subsistence in prehistoric northern Fennoscandia (Günther et al . : supplement S1 text), but they might have been important for key nutrients such as vitamin C (Bergman et al . ), and a welcome culinary supplement.…”
mentioning
confidence: 99%